Functional Responses of Prey-Predator Models in Population Dynamics; A Survey - Sambath, M.; Balachandran, K.; Surendar, M. S. (Journal of Applied Nonlinear Dynamics, 2026)
This paper presents a survey of research on the study of the impact of different functional responses on prey-predator models in ecology. These functional responses impact the qualitative behaviours of prey-predator models. Further stability and bifurcation analysis of these models are discussed. Graphical representation through numerical simulations are presented.